2010
DOI: 10.1007/s13273-010-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between nutrition intake and gene expression profiles in children with asthma

Abstract: Asthma is a complex inflammatory disease and its prevalence has increased worldwide, especially in young children. In this study, we used a '24-hour recall method' to identify differences between children with and without asthma in energy intake and energy-adjusted nutrition intake. We also performed reverse transcription-polymerase chain reaction (RT-PCR) with pathway-targeted arrays (RT2 Profiler TM PCR Array) to investigate the expression profiles of chemokines and cytokines in children with asthma. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Both ABCA1 and ABCG1 (related to cholesterol and phospholipid efflux) play a key role in severe pulmonary abnormalities such as asthma 27,28 . ABCA1-knockout mice exhibit massive lipid accumulation in alveolar macrophages, type II pneumocytes and lung parenchyma, abnormal lung morphology, and shallow breathing 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Both ABCA1 and ABCG1 (related to cholesterol and phospholipid efflux) play a key role in severe pulmonary abnormalities such as asthma 27,28 . ABCA1-knockout mice exhibit massive lipid accumulation in alveolar macrophages, type II pneumocytes and lung parenchyma, abnormal lung morphology, and shallow breathing 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The level of significance (fold change ≥ 1.3), while small, was considered significant as previous studies have shown that dietary intervention(s) tend to elicit somewhat modest, yet biologically meaningful, transcriptional responses [24,25]. The ID rats in each group exhibited modest, but significant alterations in the expression of genes representative of glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Increased Gck expression has been shown increased on the glucose levels as a metabolic substrate, to increase glucose phosphorylation rate in the liver, responsible for blood glucose elevations. Furthermore, Gck may involve in the multiple pathways such as glycogen synthesis, glycolysis, and de novo lipogenesis which may explain the enhancing of the glucose utilization and hyperlipidemia in the responsible to dietary ID-animals [110][111][112][113][114][115][116]. In the studies of metabolic gene expression alterations indicate an impaired hepatic insulin response in ID-animals, exhibited as insulin resistance.…”
Section: Iron Deficiency and Diabetes Riskmentioning
confidence: 99%